Tales of C++ Worlds: C++ Programming Language Game-Based Learning - nazri, amalin; Liyana, Haziqah; Hasanah, Izzati; Ibrahim, Zuraida (Multidisciplinary Applied Research and Innovation, 2024)
This paper presents the development of a game-based learning platform for the C++ programming language, integrating educational games, visualizations, and interactive challenges to create an immersive and engaging learning environment. C++ is acknowledged as a foundational language, but it can be challenging for non-computer science students. The platform helps students adapt their learning strategies and grasp the core principles of C++ programming. The application followed the ADDIE model, a research and development methodology consisting of analysis, design, development, implementation, and evaluation. The platform underwent a comprehensive evaluation to ensure quality and validity. This project targeted individuals seeking assistance in learning the C++ programming language and aimed to support their exam preparation through educational games and multimedia resources. A solution to transform the traditional learning approach of the C++ programming language is through the implementation of game-based learning. This innovative approach will guide learners through each level and step of the language, gradually progressing from introductory concepts to more complex topics or chapters. Unity apps serve as the foundation for C++ programming applications. Through a pilot study, the platform demonstrated positive effects on students' motivation, engagement, and learning outcomes. This research contributes to computer science education by showcasing the potential of game-based learning as an innovative approach to teaching C++ programming. Future work will focus on expanding the platform's content and conducting further evaluations to validate its effectiveness across diverse learner populations.